Implikasi Wanita Karier terhadap Pendidikan Anak - Erlidawati Erlidawati (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2021)
This article discusses the involvement of career women in educating children which is reviewed from the literature. With the development of science and technology (IPTEK) which is increasingly advanced, it leads to the advancement of a broad mindset and knowledge for everyone. The aims of this article to is determine the involvement of career women or mothers in children's education. Career women or working women are women who have a high education to get an opportunity in working with various professions. Islam does not prohibit women from working outside the home to get workers the same rights as men. However, women must be accustomed to having dual roles as working women and mothers in educating their children because the main task of women is to educate and guide their children to become mature and useful human beings for them and others. Education that must be owned by a child is; physical and spiritual education, aqidah and moral education, worship education, intellectual and economic education.